The Effect of Education Level, Investment, Capital Expenditure and Economic Growth on Unemployment Rates in Palangka Raya City - Yenie (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2019)
This study aims to determine and analyze; the effect of formal education level, increase in investment, increase in capital expenditure and economic growth on the unemployment rate in Palangka Raya City. The research method used in this study is a statistical approach, multiple linear regression analysis. This research was carried out in the City of Palangka Raya and the location of this research was carried out in the City of Palangka Raya at the Education Office of the City of Palangka Raya, the Office of Investment and Integrated Services of the City of Palangka Raya, and the Central Bureau of Statistics of the City of Palangka Raya, Secondary data for 2005-2020 obtained by research library methodThe results showed that of the four variables analyzed there were three that had a significant effect on reducing the unemployment rate, namely education, investment and economic growth. While the variable amount of capital expenditure has no significant effect and tends to be positive